Enhancing Listening Comprehension In Grade XI-D at MAN 2 Jember through Note-Taking Techniques - Avinia Prismantikasari; Tanzil Huda; Fitrotul Mufaridah (Journey: Journal of English Language and Pedagogy, 2025)
Listening comprehension is a crucial skill in language learning,. But many students continue to struggle with understanding spoken information due to cognitive overload, difficulty identifying key points, and ineffective note-taking strategies. A preliminary observation in Class XI D at MAN 2 Jember revealed that students faced significant challenges in listening tasks, as shown by their low average pre-test score of 52.5. These difficulties highlighted the urgent need for targeted instructional strategies like Classroom Action Reserach to support their listening development. This classroom action research (CAR) was conducted to investigate the effectiveness of sentence and abbreviation note-taking techniques in improving students' listening comprehension. Implemented over two cycles involving planning, acting, observing, and reflecting stages, the study demonstrated a significant improvement in students’ performance, with the average score rising to 75.9 in Cycle 2, surpassing the success criterion of 70. The findings suggest that structured note-taking techniques enhance students’ ability to extract key information and reduce cognitive overload. By addressing challenges such as classroom arrangement, phonological interference, and divided attention, the study provides practical insights for teachers seeking to improve students' listening skills through effective note-taking strategies.